Legal Protection for Patient Privacy against the Misuse of Social Media by the Healthcare Workers - Haque, Amarta Yasyhini Ilka; Susila, Muh Endriyo (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2023)
Social media initially created as a means of communication and interaction, has also evolved into a medium for transactions and expression. Social media users come from various backgrounds, including those in the health care sector. The use of social media as a means of expression by healthcare workers has the potential to harm patients, particularly concerning privacy violations. Several health care workers have faced public criticism due to their social media posts, which are deemed to infringe upon patient privacy. This paper discusses the importance of legally protecting patient privacy against the misuse of social media by healthcare workers in Indonesia. The research employs normative legal research methods with a statutory and comparative approach. The author has reviewed statutory regulations in the healthcare sector and other relevant rules. The research findings indicate that current laws and regulations in Indonesia do not offer sufficient legal protection to patients against the potential misuse of social media by healthcare workers that violates their privacy. The author recommends the implementation of special provisions to safeguard patient privacy against the misuse of social media by healthcare workers. This can be achieved by creating new or amendments to existing regulations, including legal regulations and codes of ethics. AbstrakMedia sosial yang pada awalnya diciptakan sebagai sarana komunikasi dan interaksi, dalam perkembangannya telah dimanfaatkan pula sebagai media transaksi maupun sarana berekspresi. Pengguna media sosial berasal dari berbagai kalangan, termasuk mereka yang bekerja di bidang pelayanan kesehatan. Penggunaan media sosial sebagai sarana berekspresi oleh tenaga kesehatan berpotensi menimbulkan kerugian pada pihak pasien, khususnya terkait pelanggaran privasi. Beberapa tenaga kesehatan mendapatkan kecaman publik karena unggahannya di media sosial yang dianggap melanggar privasi pasien. Artikel ini membahas pentingnya perlindungan hukum privasi pasien terhadap penyalahgunaan media sosial oleh tenaga kesehatan di Indonesia. Artikel ini menggunakan metode penelitian hukum normatif dengan pendekatan undang-undang dan perbandingan. Penulis telah mengkaji peraturan perundang-undangan di bidang kesehatan dan peraturan lain yang relevan. Hasil penelitian menunjukkan bahwa peraturan perundang-undangan yang ada di Indonesia saat ini belum memberikan perlindungan hukum yang memadai kepada pasien dari potensi penyalahgunaan media sosial oleh tenaga kesehatan yang bersifat melanggar privasi. Penulis merekomendasikan perlunya dibuat ketentuan khusus untuk melindungi privasi pasien dari penyalahgunaan media sosial oleh tenaga kesehatan, baik dengan cara menyusun peraturan baru atau mengamendemen peraturan yang telah ada, baik peraturan hukummaupun kode etik.